Social network plasticity in children - Fuentes, Miguel Angel (2018)
Converging evidence demonstrates that social relationships are crucial for healthy development during childhood. Given the high behavioral plasticity in children, in the present work we seek to evaluate whether an intervention including cooperative and mindfulness based activities could improve social relationships in middle-aged children. Thus, the aim of this study is to quantitatively analyze the impact of this kind of intervention on social networking in 6-7 year olds. In a school context, we conducted a three month intervention in a class (experimental group), which involved 24 participants. Another class of 20 children was randomly assigned as control group, which followed the usual school program. Social networks were compared before and after the intervention by means of a questionnaire asking each child to mention which peers they would like to play with, and which they do not. After the intervention, social network analysis showed an increase in the number and diversity of positive links between peers, and a reduction in negative ones. We also found a higher level of integration, indicated by enhanced positive networks where children with many positive connections tended to connect with those with few links, there were also more positive links between genders. This favorable change could reflect an increase in children’s awareness of themselves and others, fostering the emergence of collaboration and empathic concern. The methodology used here shows how quantitative methods coming from complexity science can be applied to social systems in order to, for example, promote cooperation and avoid bullying.